Rozhovory v Komenském Tucet zamyšlení o výchově a vzdělávání - Lojdová, Kateřina (Reflexe, 2022)
Title in English: Interviews in the Comenius Journal: A Dozen Reflections on Education The book includes twelve interviews about pedagogical, curricular and didactic topics conducted with leading experts and important personalities in contemporary Czech pedagogy. It captures the ways of thinking about these issues in the second decade of the 21st century. It is intended for the wide professional public - academics, teachers and students.